Understanding the role of men in women's use of the vaginal ring and oral PrEP during pregnancy and breastfeeding: multi-stakeholder perspectives. Issue 4 (2nd October 2022) - Musara, Petina; Hartmann, Miriam; Ryan, Julia H; Reddy, Krishnaveni; Ggita, Joseph; Mutero, Prisca; Macagna, Nicole; Taulo, Frank; Mgodi, Nyaradzo M; Piper, Jeanna; van der Straten, Ariane
Abstract : We examined men's influence on women's interest in biomedical HIV prevention during pregnancy and breastfeeding through structured questionnaires and focus group discussions with currently or recently pregnant and breastfeeding (P/BF) women ( n = 65), men with P/BF partners ( n = 63) and mothers/mothers-in-law of P/BF women ( n = 68) in eastern and southern Africa. Data were transcribed, coded and summarised into analytical memos. Men were depicted by most participants as joint decision-makers and influencers of women's use of HIV prevention. Cultural and religious norms depicting men as heads, breadwinners and protectors of the family were cited to legitimise their involvement in decision-making. Male partner education and engagement were recommended to garner their support in women's HIV prevention. This study elucidates how P/BF women's ability to prevent HIV is shaped by traditional and contemporary gender norms in social settings and locations where the study was conducted. Findings may aid intervention design to engage men for P/BF women's effective use of microbicide and oral PrEP.